Social and economic conditions of municipal hook and line fishermen in selected coastal barangays of Hamtic, Antique - Baldevia, Joan R.
This paper aims to determine the social and economic conditions of municipal hook and line fishermen and to identify the problems of the municipal hook and line fishermen. This would help significantly on understanding the social and economic status of the municipal fishermen. The information gathered and the derived conclusions would greatly help not only the locale government in policy making and program planning but also the fishermen in organizing their resources more efficiently. The locale of the study are the selected coastal barangays of Hamtic, Antique namely Brgy. Caridad, Mapatag and Asluman. Any conclusions in this study is only applicable to the area concerned by this fishing gear and does not apply to other fishing grounds. The basic unit pf analysis of determination of the social and economic condition were the households of the municipal fishermen. Personal and background information were gathered to determine the characteristics of the respondents. Standard of living was measured but household income. The Engel's coefficient, which is the percentage of total expenditures on food to total expenses, was used as an absolute measure of welfare. There were 52 municipal hook and line fishermen as the determined sample population, The simple random sampling was used in collecting the data and an interview schedule consisting of close and open-ended questions was used as a means in collecting the data. Simple frequency counts, percentage and averages were basically used to describe the socio-economic conditions level of the municipal fishermen. Findings of the study showed that the average income of the municipal household was PhP 4168 which was below the average monthly income in Region VI, which was PHP 5339.8. They can be considered absolutely poor however because their average monthly income was still higher to the regional poverty threshold which was PhP 8197/year. Food was the biggest cost outlay of the municipal household which accounted for 68% of the total household expenses. In terms of lot ownership, majority of the respondents owned the lot where their house was built. This was in contrast to Brgy. Caridad were majority were squatting on private lot. The type of house of the respondents were relatively made up of light materials. For their source of light and water, majority had piped-water and electricity. For cooking facility, majority still used wood which was combined with other cooking facilities such as gas and charcoal. The primary problem of the municipal fishermen was the presence of big fishing vessels like the baby purse seiner. Other problems mentioned were the illegal fishing operations like trawling which operate during the night, lack of capital for repair and maintenance and bad weather conditions. These problems further contribute to the worsening status of the municipal fishermen that the government should address these problems. The improvement of the socio-economic conditions of the fishermen should call for a general improvement of the environment in which they operate. Fishing effort should be controlled by regulation f entry in terms of number of boats or gears employed because of economic overfishing. large scale fishing like the baby purse seiner should be regulated and trawling be effectively prohibited to increase the resource base of the small-scale fishery. A clear boundary line should then be put up to avoid encroachment of the big fishing vessels to the municipal waters.